Review of Istanbul: Between the Global and the Local by Ca-lar Keyder, ed. (Lanham, MD.Rowman and Littlefield Publishers, Inc., 1999. 201 pages) (American Journal of Islam and Society, 2001)
With the picture of the city's skyline on its cover revealing the closeproximity of the golden arches of a McDonalds to the dome and minaret ofa mosque, this book automatically takes on the assumed conflict betweenIslam and the West as the backdrop to its discussion of the globalizationof Istanbul. Recognizing globalization as the current paradigm of socialchange for third world countries disillusioned by the failure of modernization,Keyder does describe Istanbul as a global city, but more so in the senseof an historical location of opposition than a truly "important node in the*global economy." He emphasizes that the city has experienced "adifferent kind of economic globalization," with the typical global-cityperspective failing to explain its evolution and Present-day conflicts. Notonly does corruption run rampant, but defensive, localist attitudes alsoprevail in regards to issues related to the cultural change associated withglobalization. Thus, while Istanbul is recognized as having the potential forbecoming a global city, this potential, generally remains unfulfilled ...